Lipid and carbohydrate metabolism disturbances in children with chronic hepatitis C - A. O. Nikiforova; V. A. Greshnyakova; A. A. Zhirkov; L. A. Alekseeva (Журнал инфектологии, 2024)
Aim. To study the state of lipid and carbohydrate metabolism, body composition, liver parenchyma structure in children with chronic hepatitis C (CHC).Materials and methods. 63 children with CHC examined at DNACIB in 2022–2023 (anthropometry, laboratory examination, bioimpedance analysis (BIA) of body composition, liver elastography with evaluation of steatosis).Results. Abnormalities of lipid metabolism were detected in 1/3 of children with CHC even with normal and low body mass index (BMI). Signs of insulin resistance (HOMAIR>3,2) were found in 54% of children with CHC. One third of patients with insulin resistance have liver steatosis, which significantly exceeds the frequency of steatosis registration among children without insulin resistance. There was a tendency for the frequency of insulin resistance to increase in proportion to the progression of the stage of liver fibrosis. No association between hepatitis virus genotype and disorders of lipid and carbohydrate metabolism was found.Conclusion. As a result of hepatitis C virus exposure in children with CHC, the risk of insulin resistance formation increases, which may be one of the pathogenetic mechanisms of liver steatosis development, increasing the risk of severe liver fibrosis formation and unfavorable outcome of the disease.